THE IMPACT OF SCHOOL LEADERSHIP AND SCHOOL VISION AND MISSION ON ACADEMIC ACHIEVEMENT WITH STUDENT SATISFACTION AS A MEDIATING VARIABLE - Andriani Sariwardani; Ikha Salhah; Suandi Silalahi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the impact of school principal leadership and school vision and mission on academic achievement, with student satisfaction as a mediating variable. The research is motivated by the critical role of leadership and strategic direction in shaping an effective learning environment, as well as how student satisfaction can strengthen these relationships. The study was conducted at SDN Bayongbong using a quantitative approach. The research method employed was a survey using questionnaires distributed to students, teachers, and school staff. Data collection techniques included observation, interviews, and documentation to support the quantitative data. The results show that both principal leadership and the clarity of the school’s vision and mission have a significant positive effect on students’ academic performance. Furthermore, student satisfaction was found to mediate this relationship, indicating that higher student satisfaction enhances the influence of leadership and vision-mission on academic outcomes. These findings underscore the importance of strong strategic leadership and the formulation of an inclusive, student-centered vision and mission.